Republic of Belarus : Technical Assistance Report-Monetary Policy Modeling. (IMF Staff Country Reports; Country Report ;, 2020)
The National Bank of the Republic of Belarus (NBRB) visited Minsk during for the seventh of the planned eight short-term technical assistance (TA) missions to help the NBRB enhance its modeling, forecasting and policy analysis capacity, and the forecasting and policy analysis system, sponsored by the Swedish International Development Agency. The NBRB is reforming its monetary policy framework in line with recommendations of past IMF TA missions and its Road Map for Transitioning to Inflation Targeting with the aim of eventually adopting inflation targeting (IT). Transitioning to IT would require, among other strengthening the monetary policy forecasting and analysis system (FPAS) and better integrating the core quarterly projection model (QPM) into the decision-making process. The mission was mainly aimed at helping with reviewing the initial conditions and compiling a QPM-based forecast as a part of the NBRB's September forecasting round. The mission, in addition, worked on strengthening processes within the FPAS.